Mycotoxins in food : Occurrence, importance and health risk - Degen, Gisela H (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2017)
Mycotoxins are produced by a variety of fungal species on crops or stored commodities; they appear as primary or secondary contaminants and via the carryover effect in the food chain. The global occurrence of many mycotoxins with a wide spectrum of toxicities is the subject of interdisciplinary research and a relevant topic for consumer protection. This overview aims to raise interest with sections of the hazardous properties of important mycotoxins (from aflatoxin to zearalenone) and describes recent developments in the area of exposure assessment and basic principles applied in risk characterization. Challenges with regard to new insights about modified and so far unregulated mycotoxins are also addressed.